2015
DOI: 10.1111/neup.12262
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐brain barrier damage in vascular dementia

Abstract: New findings on flow or drainage pathways of brain interstitial fluid and cerebrospinal fluid have been made. The interstitial fluid flow has an effect on the passage of blood-borne substances in the brain parenchyma, especially in areas near blood-brain barrier (BBB)-free regions. Actually, blood-borne substances can be transferred in areas with intact BBB function, such as the hippocampus, the corpus callosum, periventricular areas, and medial portions of the amygdala, presumably through leaky vessels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 81 publications
0
59
0
1
Order By: Relevance
“…One of the major barriers limiting the blood direct contact with the CNS is the blood-brain barrier (BBB). The BBB is built up by endothelial cells, which are interconnected by an elaborate network of tight junctions, completely encircling the lumen; perivascular endfeet of astrocytes, which cover the abluminal surface of the microvascular basement membranes; and pericytes, which have been suggested to regulate endothelial cell proliferation, survival, migration, differentiation, and vascular branching (Ballabh et al, 2004;Hellström et al, 2001;Ueno et al, 2015). Together, they form a diffusion barrier that selectively excludes most blood-borne substances from entering the brain (Martins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major barriers limiting the blood direct contact with the CNS is the blood-brain barrier (BBB). The BBB is built up by endothelial cells, which are interconnected by an elaborate network of tight junctions, completely encircling the lumen; perivascular endfeet of astrocytes, which cover the abluminal surface of the microvascular basement membranes; and pericytes, which have been suggested to regulate endothelial cell proliferation, survival, migration, differentiation, and vascular branching (Ballabh et al, 2004;Hellström et al, 2001;Ueno et al, 2015). Together, they form a diffusion barrier that selectively excludes most blood-borne substances from entering the brain (Martins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] The pathology of small vessel disease includes microvascular rarefaction, [37][38][39] neurovascular dysfunction, 40 and disruption of the blood-brain barrier. 41,42 It is estimated that 60-90% of AD patients have significant cerebrovascular pathology. 43 Hainsworth and Markus 44 identified four key clinicopathologic hallmarks of cerebral small vessel disease: small, discrete infarcts within the brain, arteriopathy of small cerebral vessels, diffuse damage to the white matter, and cognitive impairment.…”
Section: Cerebrovascular Function and Admentioning
confidence: 99%
“…Ueno et al (2016) reported that the barrier properties of the olfactory bulb deteriorate in pre-clinical rodent models of dementia including SAMP8 mice, findings consistent with clinical studies that suggest deterioration in olfaction as amongst the earliest indicators of cognitive decline (Attems et al, 2015; Devanand et al, 2015; Marin et al, 2018). In SAMP8 mice, Soriano-Cantón et al (2015) reported that the B1-neural stem cells of the mouse sub-ependymal zone, which supports ongoing production of the olfactory bulb interneurons, are transiently expanded in young SAMP8 mice relative control senescent resistant SAMR1 mice.…”
Section: Introductionmentioning
confidence: 72%